The reality of using antibiotic of surgery and the factors that influence in General Hospital of Tra Vinh Province 2017 (Vietnam Journal of Community Medicine, 2021)
The study evaluated the reality of using antibiotic of surgery and the factors that influence in General Hospital of Tra Vinh Province: The rate of using antibiotic for patient 44.78% and for surgery patient is 100%, however, there are still exist factors that affected the use of antibiotic such as age, gender, using heal insurance. Besides, research has identified the determinants of antibiotic use: Treatment protocols, antibiotic selection decisions of patients and doctors, antibiotics supply of the Faculty of Pharmacy, updated information of drugs. Recommendations: Develop regulations on drug use, drug combination; clarify criteria for using drugs, develop quality standards and provide evaluation indicators for drug resistance. To improve management of drug use by physicians and clinical departments.
Keywords: Antibiotic use, factor influence